A 3D rGO-supported NiFe2O4 heterostructure from sacrificial polymer-assisted exfoliation of NiFe-LDH for efficient oxygen evolution reaction. (5th November 2022) - Zhang, Ping; Chen, Lin; Ge, Lei; Song, Pingan; Xie, Ruishi; Wang, Bin; Fu, Yingke; Jia, Shuyu; Liao, Ting; Xiong, Ying
Abstract: NiFe2 O4 takes an attractive potential candidate for oxygen evolution reaction (OER) catalysts, however, its usual preparation based on high-temperature calcination limits exposure of catalytically active sites. Herein, we report a new and efficient strategy for preparing NiFe2 O4 supported by three-dimensional graphene network (NFO/3DGN) electrocatalysts. Specifically, NiFe layered double hydroxide (NiFe LDH) was exfoliated to single layer by polylactic acid (PLA), single layer NiFe LDH was released when PLA was hydrolyzed, and PLA hydrolysate etched single layer NiFe LDH to NiFe2 O4 ; Meanwhile, the lamellar graphene oxide was reduced to 3DGN, so that NiFe2 O4 was loaded on 3DGN, which means the agglomeration of NiFe2 O4 could be prevented and efficient electron transmission channels for NiFe2 O4 could be provided due to 3DGN. The as-prepared NFO/3DGN-10 exhibited an excellent electrocatalytic activity and stability for OER in an alkaline solution (with a low overpotential of 272 ± 25 mV at 10 mA cm −2 with a Tafel slope of 64 mV dec −1 ). Based on theoretical calculations, the reaction energy barrier of NiFe2 O4 on the speed determination step reduced significantly owing to 3DGN. These results indicate that this facile fabrication method is a promising route for developing high-performance catalysts based on mixed metal spinel oxides supported by 3DGN. Graphical abstract: NiFe2 O4 is evenly dispersed on the three-dimensional graphene network formed by rGO, which is conducive to the full exposure of the catalytic site, and rGO can improve the smooth electron transport channel in the electrocatalytic OER process. Image 1 Highlights: Single layer NiFe LDH is directly converted to NiFe2 O4 under hydrothermal conditions. NiFe2 O4 is uniformly loaded on the three dimensional network structure formed by rGO. The NFO/3DGN nanocomposite shows an outstanding performance for OER. Offer a new strategy of preparation mixed metal spinel oxides for OER catalysts.